Guardian of the Gulf : Sydney, Cape Breton, and the Atlantic Wars - Tennyson, Brian Douglas (Book collections on Project MUSE., 2000)
One of the great untold Canadian military stories revolves around the eastern seaport of Sydney, Nova Scotia. Guardian of the Gulf offers a vivid and long overdue account of Sydney harbour's role, and the importance of its coal deposits, in North Atlantic strategy and military operations from the Anglo-French wars in the eighteenth century to the end of the Cold War in the 1990s.More than two centuries of activity in and around Sydney harbour came to a head during the world wars, when Sydney became a major convoy port in the merchant-ship lifeline that sustained Britain with supplies from North America. Essential to the air and naval forces that pursued German submarines in the waters off the coast of Canada, Sydney was also an imporatant industrial centre that produced enormous quantities of critically important coal and steel. Exploring the roles of army, navy, air force, and merchant marine, Tennyson and Sarty offer richly detailed information on garrisons, fortifications, base development, and maritime warfare.Set against the Backdrop of national and alliance policymaking in London, Ottawa, and Washington, the story moves deftly between the larger and smaller pictures, making this a work of both colourful immediacy and broad interpretation.Winner of the 2000 Keith Matthews Award for Best Book, awarded by Canadian Nautical Research Society.